Seorang Wanita dengan TB Paru Kasus Baru dan TB Ekstra Paru Multiple : [New Case of Pulmonary and Multisite Extrapulmonary Tuberculosis in a Woman: A Case Report] - Gandhi Estrada Atmanto; Daniel Maranatha (Faculty of Medicine Universitas Airlangga, 2019)
Background; Tuberculosis (TB) is a contagious disease caused by Mycobacterium tuberculosis (Acid-Fast Bacilli/AFB) that still be a world burden. Extra Pulmonary TB occurred when there were infection and development of Mycobacterium tuberculosis outside lungs, which about 10% cases was Milliary TB. There will be reported case with Lung TB New Case coexistence with Multiple Extra Pulmonary TB. Case; A female, 39 y.o., came to the Soetomo General Teaching Hospital with chief complaint body weakness since 12 months ago following with cough, decrease of appetite, decrease of body weight, low grade fever, and night sweating. The cough was on and off, not productive, and didn`t improve with usual therapy. Her other complaint were painless mass at the left supraclavicular area, swollen and pain at the right knee, and pain at the backbones. Patient had subsequently given Anti Tuberculosis Drugs (ATD) with Streptomycin injection based on clinical judgement. Discussion; In several cases, Primary Focus as the result of AFB infection in the lung can spread to the other organs. The diagnosis had been made from comprehensive summary of clinical aspects, radiology data, laboratory data, and Histopathology data. Consideration of ATD choice based on grouping of TB diseases (Pulmonary/Extra Pulmonary), severity level of Extra Pulmonary TB and clinical judgement Conclusion; Had reported female patient diagnosed with Lung TB New Case, Osteomyelitis TB, Spondilitis TB, and Lymphadenitis TB. Based on therapeutic evaluation there was improvement condition of the patient after administration of ATD and injection of Streptomycin.